2009
DOI: 10.1001/archinternmed.2009.394
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Analysis of Rofecoxib Placebo-Controlled Clinical Trial Data

Abstract: Background In September 2004, rofecoxib was voluntarily withdrawn from the worldwide market. Our objective was to determine whether and when analysis of published and unpublished placebo-controlled trials could have revealed cardiovascular risk associated with rofecoxib before its withdrawal as an example to inform future post-market pharmaceutical safety surveillance efforts. Methods We conducted a cumulative subject-level pooled analysis of data from all randomized, placebo-controlled trials of rofecoxib c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…COX-2 inhibitors decreased, likely a result of rofecoxib being taken off the market in 2004. 27 On the other hand, use of narcotic analgesics rose from 1999–2000 to 2011–2012: while their increasing use may raise concern about the potential misuse/abuse of these drugs, it should be noted that use leveled off after 2003–2004. This flattening trend may reflect increased awareness of prescription opioid drug misuse/abuse, 28 although under-reporting of these drugs may have increased with awareness regarding their potential for abuse.…”
Section: Commentmentioning
confidence: 99%
“…COX-2 inhibitors decreased, likely a result of rofecoxib being taken off the market in 2004. 27 On the other hand, use of narcotic analgesics rose from 1999–2000 to 2011–2012: while their increasing use may raise concern about the potential misuse/abuse of these drugs, it should be noted that use leveled off after 2003–2004. This flattening trend may reflect increased awareness of prescription opioid drug misuse/abuse, 28 although under-reporting of these drugs may have increased with awareness regarding their potential for abuse.…”
Section: Commentmentioning
confidence: 99%
“…7476 We found that pooling clinical trial data demonstrated progressively increased cardiovascular risk as early as December 2000 and reached a P value of 0.05 by June 2001, nearly 3 and a half years before the manufacturer’s voluntary market withdrawal. 73 This issue is similarly illustrated by the recent controversy surrounding oseltamavir (Tamiflu). In the process of updating Cochrane Collaborative systematic review, several important research data inconsistencies were found.…”
Section: Promoting Transparencymentioning
confidence: 98%
“…73 We were interested in whether the drug’s cardiovascular risk could have been identified before its withdrawal, despite there being three previously-conducted company-sponsored meta-analyses demonstrating no increased risk. 7476 We found that pooling clinical trial data demonstrated progressively increased cardiovascular risk as early as December 2000 and reached a P value of 0.05 by June 2001, nearly 3 and a half years before the manufacturer’s voluntary market withdrawal.…”
Section: Promoting Transparencymentioning
confidence: 99%
“…For example, the cardiovascular risk associated with rofecoxib (Vioxx) was not apparent for several years after drug approval and eventually led to its market withdrawal. 83 Similarly, nearly a decade had passed after the approval of rosiglitazone (Avandia) before the risk of acute myocardial infarction was identified. 84 More recently, dronedarone (Multaq), a drug used to restore sinus rhythm and reduce hospitalization or death in intermittent atrial fibrillation, 85 was found to increase risk of heart failure, stroke, and death from cardiovascular causes in patients with permanent atrial fibrillation.…”
Section: Additional Features Of the Medical Device Approval Processmentioning
confidence: 99%